2012
DOI: 10.1002/pds.3319
|View full text |Cite
|
Sign up to set email alerts
|

Validity of health plan and birth certificate data for pregnancy research

Abstract: Purpose To evaluate the validity of health plan and birth certificate data for pregnancy research. Methods A retrospective study was conducted using administrative and claims data from 11 U.S. health plans, and corresponding birth certificate data from state health departments. Diagnoses, drug dispensings, and procedure codes were used to identify infant outcomes (cardiac defects, anencephaly, preterm birth, and neonatal intensive care unit [NICU] admission) and maternal diagnoses (asthma and systemic lupus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
114
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 119 publications
(123 citation statements)
references
References 18 publications
(41 reference statements)
7
114
2
Order By: Relevance
“…In addition , there may be limitations to the validity of birth certificate data included in the RI-PRAMS. Previous studies examining the validity of birth certificate data have had mixed results (53-55). The rates of PPD symptoms reported in this study represent self-reported postpartum depressive symptomatology and may not reflect a clinical diagnosis of postpartum depression diagnosis or actual rates of PPD among women with and without disabilities.…”
Section: Discussionmentioning
confidence: 99%
“…In addition , there may be limitations to the validity of birth certificate data included in the RI-PRAMS. Previous studies examining the validity of birth certificate data have had mixed results (53-55). The rates of PPD symptoms reported in this study represent self-reported postpartum depressive symptomatology and may not reflect a clinical diagnosis of postpartum depression diagnosis or actual rates of PPD among women with and without disabilities.…”
Section: Discussionmentioning
confidence: 99%
“…18 A validation study showed high positive predictive value (PPV) for selected maternal medical conditions and birth certificate variables. 19 For the current study, a programmer at the lead site wrote SAS programs that were implemented at other sites, yielding deidentified summary data that were returned to the lead site for analysis.…”
Section: Overviewmentioning
confidence: 99%
“…Studies include the examination of obstetric estimate of gestational age in California 7 and two additional states; 8 pre-pregnancy weight and height in Florida; 9 Medicaid coverage for delivery in Iowa, 10 California, 11 and two additional states; 8 and gestational diabetes in several states. 5,8,[12][13][14][15] The most comprehensive evaluation of the 2003 birth certificate, conducted by NCHS, in a total of eight hospitals in two states, found wide variation in the quality of data by item and hospital. We sought to expand the current evidence of the validity of items on the 2003 birth certificate by conducting a validation study in two geographically and demographically distinct jurisdictions-New York City (NYC) and Vermont.…”
mentioning
confidence: 99%